Penerapan Model Pembelajaran Kontesktual Untuk Meningkatkan Kemampuan Menulis Cerpen Mahasiswa PGSD - Shofiani, Arisni Kholifatu Amalia; Nugraha, Alfian Setya; Sulton, Agus; Sari, Raras Hafiida; Raharjo, Resdianto Permata (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This research aims to improve the short story writing skills of second semester PGSD UNHASY students in the literary appreciation course using a contextual learning model. Through this research, it is hoped that in the learning process in Indonesian language courses, obstacles during the learning process, student achievement before and after using the contextual learning model and its effectiveness in improving short story writing among students. This research uses a type of classroom action research (PTK). The steps for implementing the research were carried out in four stages, namely: planning, acting, observing and reflecting. The subject of this research is the process of learning to write poetry in the Indonesian language course, while the research object is second semester students majoring in PGSD, Hasyim Asy'ari University Jombang. Data collection techniques use observation techniques, tests, documentation and field notes. Data analysis techniques use quantitative and qualitative data. The indicators of success in this research are first, student activities in literary appreciation lectures on short story writing material using a contextual learning model. The results of the recapitulation of completion in cycle I and cycle II can be concluded that the contextual learning model has been successful in increasing the active and enthusiastic role of students in writing short stories.